2008
DOI: 10.1016/s1573-5214(08)80029-2
|View full text |Cite
|
Sign up to set email alerts
|

Institutional design of agri-environmental contracts in the European Union: the role of trust and social capital

Abstract: Assessing potential uptake of agri-environmental schemes based on farm and farmer characteristics only results in an incomplete analysis because it neglects the effects of motivational issues of the institutional design of contracts, as set up by the government, and of social capital. In this paper we describe contract choice using a trivariate probit model and taking into account farm and farmer characteristics and motivational issues. Motivational issues in this study include the perception of institutional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 27 publications
3
46
1
2
Order By: Relevance
“…Private consultants often rather provide production centered agricultural advice. Agri-environmental advice can be differentiated from the provision of pure agricultural advice as the latter focuses mostly on improving overall commodity production practices and potentially adversely affects the environmental effectiveness of AEMs [47,51,52]. Therefore, agricultural advice should also cover agri-environmental concerns [47,53], not least because sustainable farming practices as prescribed by AEMs require skills and knowledge [54].…”
Section: Provision Of Social Network and Agri-environmental Assistancementioning
confidence: 99%
“…Private consultants often rather provide production centered agricultural advice. Agri-environmental advice can be differentiated from the provision of pure agricultural advice as the latter focuses mostly on improving overall commodity production practices and potentially adversely affects the environmental effectiveness of AEMs [47,51,52]. Therefore, agricultural advice should also cover agri-environmental concerns [47,53], not least because sustainable farming practices as prescribed by AEMs require skills and knowledge [54].…”
Section: Provision Of Social Network and Agri-environmental Assistancementioning
confidence: 99%
“…Such a percentage has the largest effect compared with other variables. As the coordinator represents the social capital of the contract establishment, this finding seems to be reciprocal with the explanation of the role of trust and social capital as studied by Polman and Slangen (2008). They found that besides farm and farmer characteristics, motivational issues, including the perception of institutional design, the use of extension services, and trust in the government, are important for agriculture contract development, although not all types of contracts are significantly influenced.…”
Section: Farming Characteristics and Farmers' Decision Towards Contractmentioning
confidence: 90%
“…It should be noted that trust turns out to be one of the important factors explaining why contracts fail or succeed. Polman and Slangen (2008) suggested that trust in government is needed for farmers to take part in AES. In this paper, a successful contract is considered to be one which delivers the desired outcome (i.e.…”
Section: Sustaining Biodiversity With Neo-classical Contractsmentioning
confidence: 99%